SAT0023 Direct-acting antiviral-based therapy restores immune tolerance in hepatitis c-induced cryoglobulinemia vasculitis. (15th June 2017) - Comarmond, C; Garrido, M; Desbois, A-C; Costopoulos, M; Le, M Garff-Tavernier; Ahmed, SN Si; Alric, L; Fontaine, H; Bellier, B; Maciejewski, A; Rosenzwajg, M; Klatzmann, D; et al.
Abstract : Objectives: Interferon-free direct-acting antiviral (DAA)-based therapy has proven to be very effective in patients with hepatitis C virus-cryoglobulinemia vasculitis (HCV-CV). However, their mechanisms of action and their effects on cellular immunity remain poorly defined. Methods: 27 HCV-CV patients treated with DAA therapy, 12 healthy donors (HD) and 12 HCV were included. We investigated the effects of DAA-based therapy on cellular and cytokine abnormalities in HCV-CV patients by flow cytometry, cytokine Multiplex and enzyme-linked immunosorbent assay. Results: Compared with HD and HCV, pre-DAA abnormalities in HCV-CV patients included a decreased percentage of CD4 + CD25 hi FoxP3 + regulatory T cells (P<0.01) with increases in IgM + CD21 -/low memory B cells (P<0.05), CD4 + IFNγ + (P<0.01), CD4 + IL17A + (P<0.01) and CD4 + CXCR5 + IL21 + follicular helper T cells (Tfh) (P<0.01). IgM + CD21 -/low memory B cells were negatively correlated with regulatory T cells (Tregs) (P=0.03), and positively correlated with Tfh (P=0.03) and serum cryoglobulin levels (P=0.01). DAA-based therapy was associated with an increase in Tregs frequency (1.5% ± 0.18% versus 2.1% ± 0.18%), and decreased IgM + CD21 -/low memory B cells and Tfh percentage (35.7% ± 6.1% versus 14.9% ± 3.8%, and 12% ± 1.3% versus 8% ± 0.9%, respectively). B lymphocyte stimulator receptor 3 and programmed death-ligand 1 staining expression on B cells increased in HCV-CV after DAA-based therapy (MFI 37±2.4 versus 47±2.6, P<0.01; and 29±7.3 versus 48±9.3, P<0.05 respectively). Conclusions: Our results indicate that DAA-based therapy effectively normalizes many of the disturbances in peripheral B and T lymphocyte homeostasis of HCV-CV patients. Disclosure of Interest: None declared